2022
DOI: 10.1101/2022.05.23.22274942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and feasibility of fecal microbiota transplantation for Parkinson’s disease patients: a protocol for a self-controlled interventional donor-FMT pilot study

Abstract: Several experimental studies suggest a role of the gut microbiota in the pathophysiology of Parkinson’s disease (PD) via the gut-brain axis. In addition, the gut microbiota can influence the metabolism of levodopa, which is the mainstay of treatment of PD. Therefore, modifying the gut microbiota by fecal microbiota transplantation (FMT) could be a supportive treatment strategy. We developed a study protocol for a single center, prospective, self-controlled, interventional, safety and feasibility donor-FMT pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…This method to restore eubiosis in patients is called FMT. FMT has a high success rate; however, it has some low-risk and transient side effects like abdominal discomfort, bloating, diarrhea, or constipation, and the risk of infection transmission from bacterial translocation; chances of bacterial infections are low but not completely avoidable. , The use of FMT in PD is still at the initial stage, but FMT has proven beneficial in some studies where FMT, when given through colonoscopy to PD patients, was found to relieve motor and nonmotor symptoms linked with the disease. In one randomized, double-blind, placebo-controlled pilot study, when the lyophilized FMT product was orally administered to 12 subjects with mild to moderate PD and constipation, PD patients well tolerated the dose of FMT, which caused increased diversity in the intestinal microbiome and improvement in constipation, intestinal motility, and gut transit. Also, FMT improved motor and nonmotor symptoms in these cases .…”
Section: Gut-modulating Treatment Strategiesmentioning
confidence: 99%
“…This method to restore eubiosis in patients is called FMT. FMT has a high success rate; however, it has some low-risk and transient side effects like abdominal discomfort, bloating, diarrhea, or constipation, and the risk of infection transmission from bacterial translocation; chances of bacterial infections are low but not completely avoidable. , The use of FMT in PD is still at the initial stage, but FMT has proven beneficial in some studies where FMT, when given through colonoscopy to PD patients, was found to relieve motor and nonmotor symptoms linked with the disease. In one randomized, double-blind, placebo-controlled pilot study, when the lyophilized FMT product was orally administered to 12 subjects with mild to moderate PD and constipation, PD patients well tolerated the dose of FMT, which caused increased diversity in the intestinal microbiome and improvement in constipation, intestinal motility, and gut transit. Also, FMT improved motor and nonmotor symptoms in these cases .…”
Section: Gut-modulating Treatment Strategiesmentioning
confidence: 99%
“…Several preliminary clinical observations on FMT for different neurological disorders, 32 including PD, [33][34][35][36] are being published, and study protocols exploring this potential treatment for PD are being registered. 37 So far, a total of 33 PD cases have been reported, all studied in open-label fashion. [33][34][35][36] The reported patients presented with different clinical characteristics and were evaluated in different ways for variable follow-up periods.…”
Section: Fmt For Pd: Available Evidence Of Efficacymentioning
confidence: 99%
“…Several preliminary clinical observations on FMT for different neurological disorders, 32 including PD, 33 , 34 , 35 , 36 are being published, and study protocols exploring this potential treatment for PD are being registered. 37 …”
Section: Modification Of Gut Microbiota As a Treatment Strategy For ...mentioning
confidence: 99%
“…Additionally, a recent review realized by Yuanyuan Zhao et al outlines the implications of the gut microbiota in developing liver diseases such as fatty liver disease, cirrhosis, and even implications in hepatocarcinoma. This review highlights the importance of FMT by assessing the gut–liver axis in recovering from these pathologies [ 4 , 12 , 13 , 14 , 15 ]. Since specialized studies have demonstrated a change in the intestinal microbiota in patients with rheumatoid arthritis, with the frequent presence of Bacteroides , Escherichia–Shigella , and Prevotella bacteria, at Chinese PLA General Hospital, FMT was successful in a 20-year-old patient with a 5-year history of rheumatoid arthritis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%